Magnetorheological Elastomer-Based Self-Powered Triboelectric Nanosensor for Monitoring Magnetic Field - Dong Wan; Ningchen Ma; Taochuang Zhao; Xiaojing Cui; Zhaosu Wang; Hulin Zhang; Kai Zhuo (Nanomaterials, 2021)
The adaptable monitoring of the ubiquitous magnetic field is of great importance not only for scientific research but also for industrial production. However, the current detecting techniques are unwieldly and lack essential mobility owing to the complex configuration and indispensability of the power source. Here, we have constructed a self-powered magnetic sensor based on a subtle triboelectric nanogenerator (TENG) that consists of a magnetorheological elastomer (MRE). This magnetic sensor relies on triboelectrification and electrostatic induction to produce electrical signals in response to the MRE’s deformation induced by the variational magnetic field without using any external power sources. The fabricated magnetic sensor shows a fast response of 80ms and a desirable sensitivity of 31.6 mV/mT in a magnetic field range of 35–60 mT as well as preliminary vectorability enabled by the multichannel layout. Our work provides a new route for monitoring dynamic magnetic fields and paves a way for self-powered electric-magnetic coupled applications.